Spectrum of Mutations in NDP Resulting in Ocular Disease; a Systematic Review - Wawrzynski, James; Patel, Aara; Badran, Abdul; Dowell, Isaac; Henderson, Robert; Sowden, Jane C. (Frontiers in Genetics, 2022)
The inner retina is supplied by three intraretinal capillary plexi whereas the outer retina is supplied by the choroidal circulation: NDP is essential for normal intraretinal vascularisation. Pathogenic variants in NDP (Xp11.3) may result in either a severe retinal phenotype associated with hearing loss (Norrie Disease) or a moderate retinal phenotype (Familial Exudative Vitreoretinopathy, FEVR). However, little is known about whether the nature or location of the NDP variant is predictive of severity. In this systematic review we summarise all reported NDP variants and draw conclusions about whether the nature of the NDP variant is predictive of the severity of the resulting ocular pathology and associated hearing loss intellectual disability. 201 different variants in NDP have been reported as disease-causing. The pathological phenotype that may result from a disease-causing NDP variant is quite diverse but generally comprises a consistent cluster of features (retinal hypovascularisation, exudation, persistent foetal vasculature, tractional/exudative retinal detachment, intellectual disability and hearing loss) that vary predictably with severity. Previous reviews have found no clear pattern in the nature of NDP mutations that cause either FEVR or Norrie disease, with the exception that mutations affecting cysteine residues have been associated with Norrie Disease and that visual loss amongst patients with Norrie disease tends to be more severe if the NDP mutation results in an early termination of translation as opposed to a missense related amino acid change. A key limitation of previous reviews has been variability in the case definition of Norrie disease and FEVR amongst authors. We thus reclassified patients into two groups based only on the severity of their retinal disease. Of reported pathogenic variants that have been described in more than one patient, we found that any given variant caused an equivalent severity of retinopathy each time it was reported with very few exceptions. We conclude that that specific NDP mutations generally result in a consistent retinal phenotype each time they arise. Reports by different authors of the same variant causing either FEVR or Norrie disease conflict primarily due to variability in the authors’ respective case definitions rather than true differences in disease severity.